The Impact of Land Reform Policies on the Sustainable Management of Natural Resources in Local Communities - Putri, Fatma Ayu Jati; Ehsonov , Jasurbek Rustamovich (Lembaga Contrarius Indonesia, 2024)
One of the main components of the sustainable development program is land reform. At the same time, there is a lot of land conflict caused by sustainable development programs that accelerate investment through palm mining, which impacts local communities' forced takeover of land and the destruction of natural resources. The research aims to determine to what extent land reform programs impact the protection of local communities and sustainable management of natural resources. This research is descriptive, using statute, conceptual, and case approaches. As well as comparing with three countries - Indonesia, Australia, and the Netherlands - to find out the obstacles to implementing land reforms in the country. The results of this research are, first, that land reforms have a good impact on protecting local communities. However, sustainable natural resource management still takes time and consideration of some aspects. Second, there are still crucial obstacles that hinder the implementation of land reform in Indonesia, Australia, and the Netherlands. Therefore, it is crucial to adopt a participatory and collaborative approach to planning and implementing land reform programs to guarantee that the interests of all parties are addressed sustainably and equitably.